2003
DOI: 10.1128/jcm.41.7.3410-3412.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control Limits for Fluconazole Disk Susceptibility Tests on Mueller-Hinton Agar with Glucose and Methylene Blue

Abstract: An international collaborative study was performed in order to propose quality control limits for fluconazole disk diffusion susceptibility tests on Mueller-Hinton agar with 2% glucose and 0.5 g of methylene blue per ml. The supplements may be added before autoclaving the agar, or Mueller-Hinton agar plates may be flooded with a glucose-methylene blue solution. Replicate tests on both types of agar plates generated data to propose zone size limits for tests of Candida parapsilosis ATCC 22019 (22 to 33 mm), C. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…Agar plates (90-mm diameter) containing Mueller-Hinton (MH) agar (Difco Laboratories) supplemented with 2% glucose were inoculated with yeast cells, previously suspended in a saline solution (0.85%) with the turbidity 0.5 in a McFarland scale. The plates were incubated at 36 ± 1°C for 24 h. After 24 h cultivation, the inhibitory diameter zone (dz) was measured [23]. The interpretative criteria for fluconazole according to CLSI guidelines [21] were: susceptible (S) C19 mm; susceptible dose dependent (SDD) 18-15 mm and resistant (R) B14 mm.…”
Section: Antifungal Susceptibility Testsmentioning
confidence: 99%
“…Agar plates (90-mm diameter) containing Mueller-Hinton (MH) agar (Difco Laboratories) supplemented with 2% glucose were inoculated with yeast cells, previously suspended in a saline solution (0.85%) with the turbidity 0.5 in a McFarland scale. The plates were incubated at 36 ± 1°C for 24 h. After 24 h cultivation, the inhibitory diameter zone (dz) was measured [23]. The interpretative criteria for fluconazole according to CLSI guidelines [21] were: susceptible (S) C19 mm; susceptible dose dependent (SDD) 18-15 mm and resistant (R) B14 mm.…”
Section: Antifungal Susceptibility Testsmentioning
confidence: 99%
“…The proposed NCCLS method employs Mueller-Hinton agar (MHA) supplemented with 2% glucose and 0.5 g of methylene blue (GMB) per ml (4). At the present time, there is no commercial source of MHA supplemented with GMB (MH-GMB); however, MHA may be prepared and supplemented with GMB in the laboratory, or the surfaces of commercially available MHA plates may be flooded with a GMB solution (1). Although prepared and flooded plates have been shown to perform equally well in testing both fluconazole (1) and voriconazole (8), it was noted by Barry et al (1) that the shelf life of the prepared MH-GMB plates has not been established.…”
mentioning
confidence: 99%
“…Barry et al (2) have demonstrated the precision and accuracy of fluconazole disk diffusion testing and have established quality control (QC) zone diameter limits for both fluconazole and voriconazole disk diffusion tests (1,4,8) (Table 1). The proposed NCCLS method employs Mueller-Hinton agar (MHA) supplemented with 2% glucose and 0.5 g of methylene blue (GMB) per ml (4).…”
mentioning
confidence: 99%
See 2 more Smart Citations